108k views
1 vote
Simplify 8-{x-(5+x)}

1 Answer

2 votes

Answer: 13

Step-by-step explanation: 1st - Distribute the -1 through to the x + -1*(5+x) first: 8 + -1*[x + -1*(5+x)] = 8 + [-1*x + -1*-1*(5+x)]

= 8 + [-x + -1*-1 *(5+x)]

Multiply the two -1s that are in front of the (5+x). Negative x Negative = positive

Minus the paranthesis

Do PEDMAS

8 + [-x + 5 + x] <- -x +x = 0

= 8 + [0 + 5] <- 0 and 5 are like terms and will be combined

= 8 + 5 = 13

User Buksy
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.